Integrasi TPA dalam Pembelajaran melalui Kolaborasi dengan Praktisi dalam Menjaga Keseimbangan Akademik dan Non Akademik Siswa - Jannatul Radhaina; Ahmad Suriansyah; Arta Mulya Budi Harsono (CV. ITTC INDONESIA, 2025)
Current education demands a balance between pursuing academic scores and shaping students' religious character. However, full day schools often struggle to achieve this balance because students become quickly fatigued if religious lessons are placed at the end of the school day. Therefore, this qualitative research aims to deeply study how MI Al-Furqan implements the TPA (Qur'an Education Park) Integration Model and how the school collaborates with BKPMI (a practitioner organization) to maintain this balance. The findings show two main innovations: New Scheduling Arrangement and Staff Collaboration. The school moved the one-hour TPA lesson to the middle of the formal learning day, turning it into a positive break that is proven to overcome boredom, increase enthusiasm, and restore students' learning focus for the next general subjects. Collaboration with BKPMI practitioners as main teachers ensures the quality of students' Qur'an recitation and memorization (completing Iqra' volume 6 by 3rd grade). In conclusion, this model successfully resolves the time dilemma in full day school and provides a practical guide for other schools on how to use religious activities as a key driver (katalisator) that effectively boosts academic spirit and results